Serum cytokines in second trimester pregnancy and their relationship with spontaneous preterm births in the Ribeirão Preto and São Luiz cohorts - Suzana Eggers Turra; Ênio Luis Damaso; Eduardo Carvalho de Arruda Veiga; Viviane Cunha Cardoso; Heloisa Bettiol; Ricardo Carvalho Cavalli (BMC Pregnancy and Childbirth, 2023)
Abstract Objective To evaluate the association between second trimester plasma cytokine levels in asymptomatic pregnant women and preterm births (PTB) in an attempt to identify a possible predictor of preterm birth. Methods The study design was a nested case–control study including women with singleton a gestational age between 20–25(+ 6) weeks from two Brazilian cities. The patients were interviewed, Venous blood samples were collected. The participants were again evaluated at birth. A total of 197 women with PTB comprised the case group. The control group was selected among term births (426 patients). Forty-one cytokines were compared between groups. Results When only spontaneous PTB were analyzed, GRO, sCD40L and MCP-1 levels were lower in the case group (p < 0.05). Logarithmic transformation was performed for cytokines with discrepant results, which showed increased levels of IL-2 in the group of spontaneous PTB (p < 0.05). In both analyses, the incidence of maternal smoking and of a history of preterm delivery differed significantly between the case and control groups. In multivariate analysis, only serum GRO levels differed between the case and control groups. Conclusion Lower second trimester serum levels of GRO in asymptomatic women are associated with a larger number of PTB. This finding may reflect a deficient maternal inflammatory response.